Multi-Level Neuromorphic Devices Built on Emerging Ferroic Materials: A Review - Wang, Cheng; Agrawal, Amogh; Yu, Eunseon; Roy, Kaushik (Frontiers in Neuroscience, 2021)
Achieving multi-level neuro-mimetic devices is crucial to efficiently emulate key brain functionalities such as synaptic plasticity and neuronal activation, and has become an important aspect of neuromorphic hardware development. In this review article, we focus on exploiting ferromagnetic and ferroelectric materials for developing resistive devices capable of representing multiple states, and discuss the usage of such multi-level devices for implementing neuromorphic functionalities. We will elaborate that the analog-like resistive states in ferromagnetic or ferroelectric thin films are due to the non-coherent multi-domain switching dynamics, which is fundamentally different from most memristive materials involving electro-forming processes or significant ion motion. Both device fundamentals related to the mechanism of introducing multilevel states and exemplary implementations of neural functionalities built on various device structures are highlighted. In light of the non-destructive nature and the relatively simple physical process of multi-domain switching, we envision that ferroic-based multi-state devices provide an alternative pathway towards energy efficient implementation of neuro-inspired computing hardware with potential advantages of high endurance and controllability.